A low-fat diet enriched in fish oil increased lipogenesis and fetal outcome of C57BL/6 mice. Issue 2 (August 2017) - Akerele, Olatunji A; Cheema, Sukhinder K
Abstract : There is clear evidence that nutritional strategy employed during pregnancy has profound influence on the offspring health outcomes. However, the effect of the quality and the quantity of maternal fat intake on maternal metabolic profile during different stages of pregnancy and its impact on pregnancy sustainability is not known. Female C57BL/6 mice (7 weeks old) were fed diets varying in the quantity of fat (5% vs 11%) for two weeks prior to mating and throughout pregnancy. The 5% fat diet was enriched with longer chain omega (n)-3 polyunsaturated fatty acids (PUFA) from fish oil. Maternal plasma and tissues were collected before mating and during pregnancy at days 6.5, 12.5 and 18.5. Plasma lipids, glucose, insulin, progesterone and estradiol levels were measured. Cholesterol efflux capacity of maternal plasma as well as the mRNA expression of placental steroidogenic acute regulatory protein and hepatic lipogenic genes (acetyl-CoA carboxylase-1, fatty acid synthase, diacylglycerol acyltransferase-2 and stearoyl-CoA desaturase-1) was determined. Feto-placental weight and fetuses sustained throughout gestation were recorded. A low-fat maternal diet enriched with n-3 PUFA increased maternal plasma triacylglycerol and the mRNA expression of rate-limiting lipogenic enzymes, along with increasing cholesterol efflux capacity ( P  < 0.05), likely to meet fetal lipid demand during pregnancy. Furthermore, diet enriched with longer chain n-3 PUFA increased the maternal plasma concentration of progesterone and estradiol during pregnancy ( P  < 0.05), which coincides with an increase in the number of fetuses sustained till day 18.5. These novel findings may be important when designing dietary strategies to optimize reproductive capability and pregnancy outcomes.